A minimally invasive technique for correcting extra-articular malunions of metacarpal fractures - Zitao Han; Xu Zhang; Yadong Yu; Xiaoliang Yang; Wei Du; Guisheng Zhang (BMC Musculoskeletal Disorders)
Abstract Purpose This study aimed to assess the efficiency of a minimally invasive technique for correcting malunions of extra-articular metacarpal fractures, followed by percutaneous fixation using a cemented K-wire frame. Methods From January 2018 to January 2022, 31 patients (31 malunions of extra-articular metacarpal fractures) were treated. The mean age of the patients was 32 years (range, 21–52 years). There were 25 fifth, 4 fourth, 1 third, and 1 second metacarpal malunion. Range of motion of the fingers was assessed based on the total active motion scoring system of American Society for Surgery of the Hand. Range of motion of the joint was graded as excellent (85–100%), good (70–84%), fair (50–69%), and poor (< 50%) by comparing to the opposite uninjured finger. The aesthetic appearance of the hand was evaluated based on the 10-cm visual analogue scale. Patient satisfaction was assessed using the Short Assessment of Patient Satisfaction (0–10, very dissatisfied; 11–18, dissatisfied; 19–26, satisfied; and 27–28, very satisfied). Results Bone healing was achieved in all patients after a mean of 5.4 weeks (range, 4–10 weeks). The mean follow-up period was 27 months (range, 24–33 months). The mean preoperative total active motion scale was 233° (range, 185°–288°), and the postoperative scale was 263° (range, 235°–290°). There were 8 excellent, 19 good, and 1 fair result. There were 15 very satisfied and 13 satisfied with the results. The mean preoperative aesthetic appearance of the hand was 7 cm (range, 5–8 cm), and the postoperative appearance was 10 cm (range, 9–10 cm). Conclusion The minimally invasive technique is effective for correcting extra-articular malunions of metacarpal fractures. Rigid fixation allows fracture healing and early joint motion of the injured hand. The technique improves hand function, patient satisfaction, and aesthetic appearance. Level of evidence Therapeutic study, Level IVa.